2000
DOI: 10.1001/archinte.160.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Venous Thromboembolism After Deep Vein Thrombosis

Abstract: The recurrence rate after a symptomatic DVT is high. Patients with proximal DVT, diagnosed cancer, short duration of oral anticoagulation therapy, or a history of thromboembolic events had a higher risk of recurrent events, while patients with postoperative DVT had a lower recurrence rate. This knowledge could help identify patients who might benefit most from prolonged prophylactic treatment in various risk situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
366
8
17

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(416 citation statements)
references
References 21 publications
25
366
8
17
Order By: Relevance
“…29 It is estimated that a person is approximately 40 times more likely to suffer VTE within six months of their initial episode compared with a previously unaffected person (3.6 to 8.0% vs. 0.08%, respectively). 18,[30][31][32] Observational data indicate that this risk is not identical for everyone and that the risk of recurrent VTE in an individual patient can be estimated from a variety of interacting clinical, laboratory and imaging findings. 33 Although there are conflicting views as to how accurately these findings can predict one's risk, one factor which is unanimously agreed to affect VTE recurrence is the nature of the initial VTE (provoked or unprovoked).…”
Section: Recurrent Venous Thromboembolimentioning
confidence: 99%
“…29 It is estimated that a person is approximately 40 times more likely to suffer VTE within six months of their initial episode compared with a previously unaffected person (3.6 to 8.0% vs. 0.08%, respectively). 18,[30][31][32] Observational data indicate that this risk is not identical for everyone and that the risk of recurrent VTE in an individual patient can be estimated from a variety of interacting clinical, laboratory and imaging findings. 33 Although there are conflicting views as to how accurately these findings can predict one's risk, one factor which is unanimously agreed to affect VTE recurrence is the nature of the initial VTE (provoked or unprovoked).…”
Section: Recurrent Venous Thromboembolimentioning
confidence: 99%
“…35 Patients with a first symptomatic DVT have a higher risk of recurrent VTE than patients whose first event is a PE. 35,185,186 Independent predictors for VTE recurrence include advancing age, male sex, obesity, and active cancer. 26,40,60,186,187 A cohort study of patients in Olmsted County found that in multivariable adjusted analysis, the risk of VTE recurrence was increased by 17% per increase in decade of age, 24%…”
Section: Risk Factors For Recurrent Venous Thromboembolismmentioning
confidence: 99%
“…26,59,186 Prandoni and co-workers found a one-year cumulative incidence of 20.7% in cancer patients receiving conventional anticoagulants versus 6.8% in cancer-free patients on anticoagulants. 59 In the Tromsø Study, the cumulative incidence of cancer-related recurrent VTE is 2.7% (95% CI 1.0-7.0) at 30 days, 207 The risk estimates also remained equal after the first year.…”
Section: Risk Factors For Recurrent Venous Thromboembolism In Cancermentioning
confidence: 99%
“…The two major subtypes of VTE are deep vein thrombosis (DVT) and pulmonary embolism (PE). Patients who have had their first VTE episode have increased risk of recurrence,5, 6, 7, 8, 9 with the risk being highest in the first few months after the initial episode and remaining high through the first year 10. About a quarter of patients will have a recurrent episode within 5 years of their initial VTE episode and 30% are expected to have a recurrent episode within 10 years 10…”
Section: Introductionmentioning
confidence: 99%